ROOT ADHERING SOIL DAN SERAPAN KORBONDIOKSIDA TANAMAN OKRA (Abelmachus esculentus L. Moench) YANG DIBERI ECO ENZYME DAN VERMOKOMPOS PADA HISTOSOL: ROOT ADHERING SOIL AND CORBONDIOXIDE UPTAKE IN OKRA PLANTS (Abelmachus esculentus L. Moench) WHICH WAS GIVEN ECO ENZYME AND VERMOCOMPOS IN HISTOSOL - Suriani, Merti; Winarti, Sih; Murati , Ferra; Alpian, Alpian (AgriPeat, 2024)
Eco enzyme is the result of the utilization of fermentation of organic waste remaining fruit and vegetable peels, used as liquid organic fertilizer (POC). The combination of eco enzyme treatment and vermicompost as ameliorant is expected to improve the physical, chemical and biological properties of peat soil as a growing medium for okra plants (Abelmachus esculentus L. Moen). The research analyzed the effectiveness of eco enzyme and vermicompost on root adhering soil and carbon dioxide uptake of okra plants (Abelmachus esculentus L. Moench) grown on histosol. The results of the study showed that the application of POC eco enzyme and vermicompost on histosol had a significant effect on the ability of roots to hold soil (RAS), wet weight, dry weight, biomass (carbon) and carbon dioxide uptake of okra plants. The treatment of POC eco enzyme 60 ml/polybag and vermicompost 84.75 g/polybag is the ideal planting media composition and the best dose. BNJ 5% test V1E1 treatment was significantly different on carbon dioxide absorption compared to V3E3, V2E2 and V0E0 treatments